2017
DOI: 10.1007/s11250-017-1225-8
|View full text |Cite
|
Sign up to set email alerts
|

Partial or total replacement of commercial concentrate with on-farm-grown mulberry forage: effects on lamb growth and feeding costs

Abstract: Replacing commercial concentrate with mulberry foliage was evaluated in a feeding trial lasting 126 days. Forty-eight weaned male Pelibuey lambs (20.6 ± 0.80 kg of BW) were randomly allocated to four groups: (1) supplementing the basal diet with mulberry at 1% (DM basis; M-1), (2) mulberry at 0.75% plus 0.1 kg concentrate fresh matter basis (M-0.75), (3) mulberry at 0.50% plus 0.2 kg concentrate (M-0.50) and (4) basal diet plus 0.3 kg concentrate (control; M-0). During the first 90 days, the basal diet was Pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…In line with the current study, Atiso et al (2012) reported that increasing total DM intake with substitution of 50% of mulberry leaves for concentrate mix compared to sole concentrate mixture supplementation in dairy cows. Nevertheless, Contrary to the present study, (Alpízar-Naranjo et al 2017)reported that the diet supplemented by sole mulberry foliage and that supplemented by whole commercial concentrate showed, respectively, the lower and higher values of total feed intake throughout the whole experimental period. The increased NDF and ADF intake as the proportion of mulberry leaf meal increases obtained in the current study suggests the relatively increased barley straw intake observed and relatively higher fiber fraction in mulberry than that of the concentrate diet.…”
Section: Feed Intakecontrasting
confidence: 99%
“…In line with the current study, Atiso et al (2012) reported that increasing total DM intake with substitution of 50% of mulberry leaves for concentrate mix compared to sole concentrate mixture supplementation in dairy cows. Nevertheless, Contrary to the present study, (Alpízar-Naranjo et al 2017)reported that the diet supplemented by sole mulberry foliage and that supplemented by whole commercial concentrate showed, respectively, the lower and higher values of total feed intake throughout the whole experimental period. The increased NDF and ADF intake as the proportion of mulberry leaf meal increases obtained in the current study suggests the relatively increased barley straw intake observed and relatively higher fiber fraction in mulberry than that of the concentrate diet.…”
Section: Feed Intakecontrasting
confidence: 99%
“…The mulberry field area of China has been estimated to be 700,000 ha, yielding substantial production of 15 to 37 t of mulberry leaves per hectare (Han, 2006). Furthermore, it is documented that the digestible energy and CP value of mulberry leaves could be as high as those of alfalfa hay (Doran and Laca, 2007), and they could partially substitute for expensive supplements in bovine diets with little damage to animal performance (Habib et al, 2016;Alpízar-Naranjo et al, 2017;Tesfay et al, 2018). Meanwhile, the mulberry plant is a conventional herb with multiple pharmacological functions (Thaipitakwong et al, 2018;Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu [6] added 15% mulberry leaf powder to the finished pigs' diet and found that it can change the muscle fiber properties, resulting in enhanced antioxidant capacity and increased intramuscular fat to improve meat quality. At present, the demand of mulberry leaves is increasing in the livestock industry [7]. However, differences in a mulberry growth environment and field management can result in quality differences of mulberry leaves [8].…”
Section: Introductionmentioning
confidence: 99%